Lighting Up Mutation: a New Unbiased System for the Measurement of Microbial Mutation Rates - Boyce, Kylie J. (mBio, 2019)
Although mutation drives evolution over long and short terms, measuring and comparing mutation rates accurately have been particularly difficult. This is especially true when mutations lead to an alteration in fitness. E. Shor, J. Schuyler, and D. S. Perlin (https://doi.org/10.1128/mBio.00120-19) present a new method to compare mutation rates across fungal strains and under different growth conditions: they employ the green fluorescent protein (GFP) as the reporter and count mutations using fluorescence-activated cell sorting (FACS). The estimates of mutation rates using the GFP-FACS approach are similar to those calculated with other reporters, and the method was used to assess if different alleles of the mismatch repair pathway gene MSH2 impact the mutation rates in the human pathogen Candida glabrata. The approach could be extended to other microbes and applications, opening the way for a better understanding of how mutation rates have impacted speciation and the emergence of antimicrobial resistance.